Structural and mechanical properties of cellulose acetate/graphene hybrid nanofibers: Spectroscopic investigations - B. S. Kim; I. S. Kim; K. Zeeshan; K. Fujimori; M. Gopiraman (eXPRESS Polymer Letters, 2013)
Cellulose acetate/graphene (CA/graphene) and cellulose acetate/graphene-COOH (CA/graphene-COOH) hybrid nanofibers were fabricated via electrospinning technique, and their morphologies, crystallinity and mechanical properties were investigated. The added amounts of graphene and graphene-COOH were varied from 0.5 to 5.0 wt%. The crystal structures and morphologies of the resultant hybrid nanofibers were investigated by wide angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively. Graphene-COOH incorporated CA nanofiber mats showed higher Young’s modulus of about 910 MPa among than those of CA/graphene nanofibers, which is due to molecular interactions between –COOH groups in acid-treated graphene and C=O groups in CA via hydrogen bonding. This specific interaction was demonstrated by spectroscopic studies (Raman and Fourier transform infrared (FT-IR) spectroscopies).